Creating Comfortable Classroom by VAK Learning Styles: Planning for Early Childhood to Interest in Learning English - Lista Litta; Astry Budiarty (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2020)
The objectives of the research were to investigate whether or not creating a comfortable classroom by VAK learning styles as a technique has significant effects for early childhood in learning English and whether or not the students are interested in creating a comfortable Classroom by VAK Learning Styles as a technique in Learning English. This research employed a pre-experimental method by using one group pre-test and post-test design, where the writer did an experiment in a single group only. The population of this research was the students of TK Tri Putri in Makassar Suburb academic year 2019/2020. This research used purposive sampling. The sample consisted of 34 students. Those students should be 5-6 years old. The data was collected by using a writing test and observation checklist. The findings showed that there was an improvement in the students’ English ability after the treatment. The students’ result of the posttest was more significantly improved than the students’ result of the pretest by the mean score of 81.18 > 50.12. The difference of both scores was statistically significant based on the t-test value at significant level 0.05 in which the P-value is lower than the significant level (0.000 < 0.05). The mean score of the students’ interest in cycle 2 was 80 and it was categorized as interested classification.